Recruitment of racial and ethnic minorities to clinical trials conducted within specialty clinics: an intervention mapping approach - Amorrortu, Rossybelle P.; Arevalo, Mariana; Vernon, Sally W.; Mainous, Arch G.; Diaz, Vanessa; McKee, M. Diane; Ford, Marvella E.; Tilley, Barbara C. (Current controlled trials in cardiovascular medicine, 2018)
Background Despite efforts to increase diversity in clinical trials, racial/ethnic minority groups generally remain underrepresented, limiting researchers’ ability to test the efficacy and safety of new interventions across diverse populations. We describe the use of a systematic framework, intervention mapping (IM), to develop an intervention to modify recruitment behaviors of coordinators and specialist investigators with the goal of increasing diversity in trials conducted within specialty clinics. To our knowledge IM has not been used in this setting. Methods The IM framework was used to ensure that the intervention components were guided by health behavior theories and the evidence. The IM steps consisted of (1) conducting a needs assessment, (2) identification of determinants and objectives, (3) selection of theory-informed methods and practical applications, (4) development and creation of program components, (5) development of an adoption and implementation plan, and (6) creation of an evaluation plan. Results The intervention included five educational modules, one in-person and four web-based, plus technical assistance calls to coordinators. Modules addressed the intervention rationale, development of clinic-specific plans to obtain minority-serving physician referrals, physician-centered and patient-centered communication, and patient navigation. The evaluation, a randomized trial, was recently completed in 50 specialty clinics and is under analysis. Conclusions Using IM we developed a recruitment intervention that focused on building relationships with minority-serving physicians to encourage minority patient referrals. IM enhanced our understanding of factors that may influence minority recruitment and helped us integrate strategies from multiple disciplines that were relevant for our audience.